ANALISIS ASPEK SUMBERDAYA YANG BERLANGSUNG PADA PROGRAM KELAS IBU BALITA DI WILAYAH KABUPATEN BANYUMAS - Pantiawati, Ika (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
One of the government's efforts to reduce infant mortality is by launching a mother's toddler class program. A mother's toddler class is a way to find out how to care for and care for babies and children who are right and can know the development of the child's age both physically and mentally. In reality there are a number of village midwives who do not know clearly the plekasanaan class of under-five mothers. Poor communication between coordinating midwives and village midwives will greatly affect the implementation of the mother's toddler class program. The purpose of this study was to analyze the Resource aspects that took place in the mother's toddler class program in the Banyumas District. This study used an observational design with a qualitative approach. The main informants were selected based on the class of toddlers' mothers who were active and inactive as well as achieving the output of the mother's toddler class. The main informants were 13 village midwives, triangulation informants were 4 coordinating midwives, 1 Sie KIA Banyumas District Health Office and 10 mothers of toddler class mothers. Data was collected by in-depth interviews and FGDs. Processing and analysis of data using content analysis. The results of the analysis of the implementation of a class of mothers of children under five from active and non-ive classes of under-five mothers were still not good. Judging from the resources that take place there is no funding specifically for the class of toddler mothers. Keywords: Resources, Toddler Mother Class Program